An Evaluation Tool for Collaborative Clinical Research Centers. Issue 3 (18th April 2013) - Tragus, Robin; Cody, Jannine D.
Abstract There is a need for metrics that describe the full range of services provided by a clinical research unit; given that services have expanded to include such things as investigator training, regulatory compliance monitoring, and budget negotiations. We developed a tool and methodology that allows tracking of these expanded services. This not only allowed us to more accurately describe the work of the research unit staff, but to monitor the status of a study across the entire study lifespan from the idea to the publication. In addition to measuring work, it allows us to anticipate future needs in clinical staff and expertise because we are involved very early in study planning. We also expect that by analyzing these data from many studies over time, we will identify process barriers that will direct future program improvement.